Numerical Study on Water Sealing Effect of Freeze-Sealing Pipe-Roof Method Applied in Underwater Shallow-Buried Tunnel - Hong, Zequn; Zhang, Jun; Han, Lei; Wu, Yuanhao (Frontiers in Physics, 2022)
The Freezing-Sealing Pipe-Roof (FSPR) method is a new pre-supporting technique, which fully combines the advantages of pipe-roof method and artificial ground freezing method, and can adapt to the construction needs of underground projects in complex and sensitive strata. After the Gongbei Tunnel of Hong Kong-Zhuhai-Macao Bridge, this method will be applied for the first time in an underwater shallow-buried railroad tunnel, and there are still many urgent problems to be solved. In this paper, based on the field situation and the preliminary design scheme, a convective heat transfer model under complex boundary conditions was firstly established. Then, the development of frozen wall thickness during the active freezing period was solved by numerical simulation for three different pipe filling modes, and the cloud map of temperature distribution in the whole section is analyzed. After that, the moving state of river water was characterized by different heat transfer coefficients, and the weakening effect of flow velocity on the top freezing wall was studied. Finally, six critical water sealing paths were selected and the temperature differences of the frozen curtain were calculated. The results show that the mode with interval concrete filling can form a reliable frozen curtain within the scheduled time, while the non-filling mode cannot achieve the water sealing requirement. River water has a large effect on the temperature at the boundary of jacking pipe and almost no effect on the center of the jacked pipe. It takes about 15 days from the frozen soil covering the pipe wall to reach the designed thickness, and the freezing effect of empty pipe lags about 28 days compared with that of solid pipe, which requires targeted enhancement measures in field projects.